2017
DOI: 10.1016/j.jad.2017.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Preconception gynecological risk factors of postpartum depression among Japanese women: The Japan Environment and Children's Study (JECS)

Abstract: CONCLUSION: Women with endometriosis and menstrual problems were at risk of developing postpartum depression. This study suggests a perinatal mental health screening for predisposed women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 58 publications
3
22
0
3
Order By: Relevance
“…Additionally, Coleman and his colleagues also found that severe menstrual pain was an important risk factor strongly associated with depression 20 . Our study suggests that parturient women with dysmenorrhea have a high risk of PPD; this result is consistent with the findings from a Japanese study that included 11,341 PPD patients and 71,148 controls 23 . Their study demonstrated that parturients with dysmenorrhea had 1.13 times higher risk of developing PPD (OR, 1.13; 95% CI: 1.06–1.21), after adjustment for socio-demographic factors, health behavioural factors, psychiatric illness history, psychosocial factors, obstetrical factors and birth outcome factors 23 .…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, Coleman and his colleagues also found that severe menstrual pain was an important risk factor strongly associated with depression 20 . Our study suggests that parturient women with dysmenorrhea have a high risk of PPD; this result is consistent with the findings from a Japanese study that included 11,341 PPD patients and 71,148 controls 23 . Their study demonstrated that parturients with dysmenorrhea had 1.13 times higher risk of developing PPD (OR, 1.13; 95% CI: 1.06–1.21), after adjustment for socio-demographic factors, health behavioural factors, psychiatric illness history, psychosocial factors, obstetrical factors and birth outcome factors 23 .…”
Section: Discussionsupporting
confidence: 92%
“…EPDS (Cox et al 1987), which comprises 10 items listed in a four-point Likert scale from 0 to 3 according to the increasing severity of symptoms, ranges from BYes, most of the time,^BYes, sometimes,^BNot very often,^to BNo, not at all.^Okano et al translated the EPDS into Japanese, backtranslated the scale, conducted the test-retest method to examine reliability, and calculated Cronbach's α (0.78) (Okano et al 1996). Okano et al reported that the appropriate cutoff point for detecting PPD was 9 or higher, with 75% sensitivity and 93% specificity (Yamaoka et al 2016;Muchanga et al 2017), whereas 12 or higher is generally used as the cutoff point worldwide (Cox et al 1987). A recent study on Japanese women has shown the optimal cutoff of EPDS score for major depressive episode during pregnancy as 12 (Usuda et al 2017).…”
Section: Variablesmentioning
confidence: 99%
“…Strategi koping dipengaruhi oleh beberapa aspek yang berbeda, seperti status sosial ekonomi, gaya koping, optimisme, keterkaitan antar penyebab stres, dan pengendalian stresor (Monzani et al, 2015). Depresi postpartum dapat terjadi mulai dari setelah melahirkan sampai satu bulan sesudahnya, bahkan sampai satu tahun (Muchanga et al, 2017). Insiden depresi meningkat secara signifikan selama tiga bulan pertama setelah ibu melahirkan, dan kejadian depresi akan meningkat tiga kali lipat lebih tinggi pada lima minggu setelah melahirkan (Kettunen, Koistinen and Hintikka, 2014).…”
unclassified